Christian women in the Greek papyri of Egypt to 400 CE - Mathieson, Erica A. (Studia antiqua australiensia, 2014)
The documentary papyri are an unparalleled source for the study of women in antiquity. Among them are numbers of female-authored texts which allow women's voices to be heard. In the period to 400 CE twenty-six of these texts provide information on Christian women's religious lives. This book analyses these papyri. They give insight into Christian women's knowledge and use of biblical texts, their practice of prayer, their theological understanding of God, their lives and relationships. This book also examines texts written to Christian women or referring to Christian women among which are a valuable group referring to ascetic women. The perspectives of the papyri nuance what is known about women from other sources.